Ambient seismic vibrations in steep bedrock permafrost used to infer variations of ice-fill in fractures - Weber, S. (S.); Fäh, D. (D.); Beutel, J. (J.); Faillettaz, J. (J.); Gruber, S. (Stephan); Vieli, A. (A.) (Earth and Planetary Science Letters, 2018)
The behavior of ice in frozen rock masses is an important control on rock slope stability but the knowledge of the formation, extent and evolution of ice-filled fractures in steep bedrock permafrost is limited. Therefore, this study aims at characterizing the site specific ambient seismic vibration recorded at the Matterhorn Hörnligrat fieldsite over the course of more than three years. The observed normal mode resonance frequencies vary seasonally with four distinct phases: persistent decrease during summer (phase I), rapid increase during freezing (phase II), trough-shaped pattern in winter (phase III) and a sharp peak with a rapid decay during the melting/thawing season (phase IV). The relation between resonance frequency and rock temperature exhibits an annually repeated pattern with hysteretic behavior. The link between resonance frequency, fracture width and rock temperature indicates that irreversible fracture d